El uso de las tics en el proceso de enseñanza aprendizaje en el área de estudios sociales en los alumnos del octavo, noveno, décimo año de educación básica del colegio nacional técnico prof Nelly Aguirre Cárdenas del cantón Santa Rosa, año lectivo 2012-2013 - Maldonado Bravo, Robison Maubricio (2013)
It must be recognized that new technologies provide teaching both economic and social benefits as cultural to the proper use also true revolution occurs with the emergence and spread on the fields to be used, since it has allowed to make available to everyone access information and even endless communication resources